Autologous stem cell transplantation in elderly multiple myeloma patients aged ≥65 years: a two‐centre Australian experience. Issue 2 (25th February 2021) - Er, Jeremy; Routledge, David; Hempton, Jennifer; Wood, Colin; Joyce, Trish; Harrison, Simon; Campbell, Philip
Abstract: There are currently limited Australian data on the outcomes of autologous stem cell transplantation (ASCT) in elderly multiple myeloma (MM) patients. We present the largest cohort of elderly MM patients aged ≥65 years undergoing ASCT in Australia and report their outcomes based on our two‐centre experience. Our study affirms that ASCT is well tolerated, safe and effective in elderly MM patients aged ≥65 years and should be considered an important component of treatment in patients who are fit enough for the procedure.